1970
DOI: 10.4314/ejhs.v29i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Time to First Line Antiretroviral Treatment Failure among Adult Patients Living with HIV in Public Health Facilities of Arba Minch Town, Southern Ethiopia

Abstract: BACKGROUND: Antiretroviral therapy is a proven medication given for Human Immunodeficiency Virus positive individuals. However, first-line antiretroviral treatment failure becomes a public health issue and early detection of treatment failure is crucial for timely actions. Therefore, this study aimed to identify the predictors of time to first-line antiretroviral treatment failure among adult patients living with HIV in public health facilities of Arba Minch Town.METHODS: Institution-based retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
2
3
1
Order By: Relevance
“…HIV-infected patients with poor ART adherence had a higher risk of death compared to those who had good ART adherence scores. This finding is agreed with the study findings from Northern Ethiopia, 26 India, 27 Arba Minch, 42 Southwestern Ethiopia, 43 and Jharkhand, India. 44 This can be due to forgetting about taking ARV drugs, late initiation of the follow-up care, lack of close supervision and counsel from adherence supporters, and follow-up interruptions due to the patients and health facility/health care worker’s factors.…”
Section: Discussionsupporting
confidence: 93%
“…HIV-infected patients with poor ART adherence had a higher risk of death compared to those who had good ART adherence scores. This finding is agreed with the study findings from Northern Ethiopia, 26 India, 27 Arba Minch, 42 Southwestern Ethiopia, 43 and Jharkhand, India. 44 This can be due to forgetting about taking ARV drugs, late initiation of the follow-up care, lack of close supervision and counsel from adherence supporters, and follow-up interruptions due to the patients and health facility/health care worker’s factors.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the odds of virological failure were higher among those who had a history of OI throughout the follow-up period compared with those who had no history of OI throughout the follow-up period. This finding is in line with the studies conducted in Jimma ( 17 ) and Arba Minch towns of Ethiopia ( 35 ) which showed patients with opportunistic infections, such as TB, appear to be at a higher risk of virological failure. This finding also consisted of a study conducted in Nigeria ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…Although the rate of VTF was higher among PLHIV who stated ART with CD4 <200 cells/mL (11.6% (95% CI: 8.1%, 15.1%)) compared to those who started ART with CD4 > = 200 cells/ mL (8.1% (95% CI:6.4%, 9.9%)), this difference was not statistically significant, p = 0.062. The failure rate of 3.7% among adults in this study was inconsistent with previous findings from studies conducted among adults in Ethiopia, Uganda, India, and Kenya [13,14,[22][23][24][25][26][27], where rates of VTF among adults ranged from about 10% to as high as 34%. Many of these studies however, used the definition of two consecutive VL >1000 copies/ml 3 3 months apart, without the condition of adherence counseling, somewhat different to the definition used in our study.…”
Section: Plos Global Public Healthcontrasting
confidence: 99%